LEGAL IDEOLOGY ON SOCIAL JUSTICE PERSPECTIVE - I Dewa Gede Atmadja (Warmadewa Press, 2021)
This research focus on study the synthetic legal ideology and social justice from legal philosophy. On literature there are debatable of legal ideology in legal philosophy, it is about meaning of justice too. According philosophy of natural law, legal ideology is legitimation of virtue people behavior and eternal justice for human being. Opposed to the philosophy of law positivism, there is no place to discuss ideology of justice in science of law, because no criteria and no reference, no argumentation about just or unjust law. Essence of justice is correct applied rule of positive law to settlement dispute, called a procedural justice or legal justice om the contrary to substantive justice. On Marxist philosophy justice is an ideology essence power for socialism community, opponent capitalistic-liberalism philosophy that justice not for all but justice and rule of law is illusion only. Hinduism philosophy there is only moral justice its dharma. The first duty of King to realized dharma, integrated politics, economics, social, and culture in reality high moral standard behavior of human being. It aims realized prosperity for people in the world. Compatible with based of State Philosophy of PANCASILA are legitimation Indonesian system of law, core aim realized â€œsocial justiceâ€. Essence distribution all national asset, taxation, regulation of wages for workers welfare, wealth, education, allocation houses and also distribution natural resources for benefit of all people of Indonesian. It regulation equality benefit constitute and accountability our Government. According The 1945 Constitution of The Republic Of Indonesia to reach Indonesian justice and prosperity.